Phenotypic and Molecular Characterization of Biofilm Formation in Clinical Pseudomonas aeruginosa Isolates and Its Association with Antimicrobial Resistance - Noor Swadi (International Journal of Health and Social Behavior, 2026)
Pseudomonas aeruginosa is a major opportunistic pathogen responsible for burns, wound, respiratory tract, urinary tract, bloodstream, and medical device-associated infections. Its ability to form biofilms contributes to persistent infections and reduced susceptibility to antimicrobial agents. This cross-sectional laboratory-based study aimed to characterize biofilm formation among clinical P. aeruginosa isolates and examine its association with antimicrobial resistance. A total of 100 non-duplicate clinical isolates were collected from selected teaching hospitals and clinical microbiology laboratories in Baghdad. Bacterial identification was performed using conventional microbiological methods and automated systems when available. Biofilm production was assessed using the crystal violet microtiter plate assay and categorized as non, weak, moderate, or strong producers based on optical density values. Antimicrobial susceptibility was evaluated using the Kirby–Bauer disk diffusion and minimum inhibitory concentration methods. Polymerase chain reaction was used to detect biofilm-related genes, including algD, pelA, pslA, and lasR. The results showed that 40% of isolates were strong biofilm producers, 30% moderate, 20% weak, and 10% non-producers. Strong biofilm producers exhibited higher antimicrobial resistance than weak and moderate producers. The algD gene was the most frequently detected, followed by pslA, pelA, and lasR. A strong positive correlation was observed between biofilm density and antimicrobial resistance, highlighting the value of combined phenotypic and molecular approaches for infection control and treatment strategies.